Neurophysiological Features of Viral Encephalitis in the Elderly Patients - D. T. Abdukadirova; M. Sh. Xojiimatova. (Periodica Journal, 2023)
Acute viral encephalitis (OVE) is characterized by severe course, high mortality rate, and high frequency of neurological complications of a disabling nature. We examined 48 elderly patients with manifestations of primary and secondary encephalitis complicated by convulsive syndrome. The presence of repeated epileptic seizures or status epilepticus that are persistent and cannot be stopped by conventional antiepileptic drugs in elderly patients with acute encephalitis requires a comprehensive clinical, electrophysiological and neuroimaging examination in the dynamics of the disease in order to determine the localization of structural changes in the brain and the possibility of preventing the development of severe complications of cerebral coma and mortality
Keywords: Encephalitis; meningoencephalitis; virus